Intussusception in a Premature Neonate: A Rare Often Misdiagnosed Cause of Intestinal Obstruction - I. Loukas; N. Baltogiannis; C. Plataras; A.-V. Skiathitou; S. Siahanidou; G. Geroulanos (Case Reports in Medicine)
Intestinal obstruction in neonatal period is an emergency caused by many surgical causes. An extremely rare surgical cause in this group of age is intussusception which can be easily confused with other surgical entities. In several reports, a significant number of the infants who were included in the study population were believed to have necrotizing enterocolitis (NEC). We present a rare cause of small intestine obstruction in a preterm female infant that can be easily misdiagnosed and confused preoperatively with other clinical entities particular for this period.